Microwave Assisted Synthesis of Ethyl 2,4-disubstitued thiazole-5-acetates for their Antioxidant Activity - Mohan, S.; Attimarad, Mahesh (Asian Journal of Chemistry, 2016)
Synthesis of ethyl 3-aroylpropionates (3-4) has been conducted under microwave irradiation in open vessels and then brominated to ethyl 3-bromo-3-aroylpropionate (5-6). Ethyl 2,4-disubstituted thiazole-5-acetates (8a-s) have been synthesized by condensing thiourea/(un)substituted phenylthiourea (7) with bromo ester (5-6) under microwave irradiation using ethanol as the microwave energy transfer agent. The synthesized compounds have been tested in-vitro for their antioxidant activity.